Reação de genótipos de arroz frente a nematoides das lesões radiculares e herdabilidade da resistência - Biela, Fábio (2013)
Rice (Oryza sativa L.) is considered one of the oldest food plants used by humans, thus becoming one of the most-produced cereal in the world. However, it is important to note that many pathogens may be limiting to the production of this crop, including the root lesion nematodes (Pratylenchus spp.), which are widespread on virtually all agricultural regions of the country. Among the control methods, which aim to reduce the population of these organisms, the use of resistant varieties is mentioned, however there is a lack of information about the response of rice genotypes to nematodes of the genus Pratylenchus. Thus, the present study aimed to evaluate the response of rice genotypes to Pratylenchus brachyurus and P. zeae. The following materials were evaluated: Cateto Amarelo, BRS Primavera, Riccetec Ecco CL, BRS Bonança, BRS Soberana, BRS Conai, IAPAR 9, Lineage L05 - A6, BRS Maravilha, Lineage L03 - 107, BRS Sertaneja, IAPAR 63, BRS Colosso, Lineage L06 - 2, BRS MG Caravela, ANA 9001, BRS Pepita, BRS Talento, BRS Serra Dourada, BRS MG Curinga, IAPAR 64 IPR 177, Lineage L06 - 1, BRS Monarca, AN Cambará e IAPAR 117. The milhet AMN 17 and maize BRAS 3010 were used as the standard of resistance and susceptibility, respectively. Naturally infested soils were used in the experiments, they were obtained from different areas, one from a crop of soybeans with a history of infestation of P. brachyurus and the other from sugarcane, with P. zeae. These soils were placed in of ruts with 1 L capacity and, initially, corn was cultured for 90 days, determining the initial population of nematodes. Later, rice genotypes were sowing, determining the factor of reproduction after 90 days of germination. Each experiment was repeated in two distinct periods. All genotypes were susceptible to P. brachyurus, but only in the second experiment there was observed a statistical difference, showing different degrees of susceptibility, whereas genotypes Lineage L03 - 107 and Cateto Amarelo had a population higher than the standard corn, with reproduction factors (RF) equal to 8.80 and 9.48, respectively. For P. zeae, first experiment done also showed different degrees of susceptibility, in which genotypes: Lineage L03 - 107 and IAPAR 9 showed RF higher than the other genotypes, including the standard corn, equal to 8.99 and 6.54, respectively. In the second experiment, all genotypes showed RFmenor1, including the standard corn, possibly due to low temperatures during the experimental period. Brod-sense heritability for both nematodes shoved low values, indicating higher environmental effect on the phenotypic variability, with low genetic variability of studied genotypes